PENGARUH DAYA REGIONAL TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT DI INDONESIA: ANALISIS DATA PANEL - Robby A. Sirait; Jesly Y. Panjaitan (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2016)
This study aims to examine the effect of regional competitiveness for the welfare of society and analyze the achievements of the determinant variables Indonesia's competitiveness and inter-regional in Indonesia. The method used in this study is Random Effect Model by using secondary data, a panel of thirty-three provinces in Indonesia from 2010 to 2014. The result indicates that competitiveness has a positive and significant correlation to the welfare of society, which is proxied by the Human Development Index (HDI).